Circulating miRNA associated with posttraumatic stress disorder in a cohort of military combat veterans. (May 2017) - Martin, Christiana G.; Kim, Hyungsuk; Yun, Sijung; Livingston, Whitney; Fetta, Joseph; Mysliwiec, Vincent; Baxter, Tristin; Gill, Jessica M.
Abstract: Posttraumatic stress disorder (PTSD) affects many returning combat veterans, but underlying biological mechanisms remain unclear. In order to compare circulating micro RNA (miRNA) of combat veterans with and without PTSD, peripheral blood from 24 subjects was collected following deployment, and isolated miRNA was sequenced. PTSD was associated with 8 differentially expressed miRNA. Pathway analysis shows that PTSD is related to the axon guidance and Wnt signaling pathways, which work together to support neuronal development through regulation of growth cones. PTSD is associated with miRNAs that regulate biological functions including neuronal activities, suggesting that they play a role in PTSD symptomatology. Highlights: Sequencing miRNAs from blood of military service members allows unbiased analysis. 8 miRNAs had differential expression in PTSD vs. control subjects. miRNAs targeted genes in Wnt signaling and axon guidance pathways. Affected pathways primarily influence neuronal development and plasticity.